Pengembangan Trainer Equalizer Grafis dan Parametris sebagai Media Pembelajaran Mata Kuliah Praktik Sistem Audio - Bekti Wulandari; Suparman Suparman; Djoko Santoso; Muslikhin Muslikhin (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The objectives of this study were to determine the development process of graphic and parametric equalizer trainer media in the course of Audio System and to examine the quality of the media. The development process of the media referred to the model offered by Lee and Owens. The research procedures consisted of assessment/analysis, designing, implementation and evaluation. The results of the study showed that the percentages for the quality aspect of the media and the companion module were 4.31 and 4.42 respectively. Based on these two aspects, it was obtained the overall percentage that was equal to 4.36. Whereas from the process of the trial by the students, the percentages of the media and the companion module were 4.47 and 4.36 respectively. Thus the level of validity and feasibility of the media was categorized as very good.